HbA1c and Pulsatility Index in Middle Cerebral Artery of Patients with Acute Thrombotic Stroke - Bintan, Rio Tasti Surpa Rahmat; Setyowati, Sita; Adrianto, Yudhi (Folia Medica Indonesiana, 2024)
Highlights: 1. The findings of this study indicate that clinicians should remain vigilant, as effective glycemic control, reflected by optimal HbA1c levels, does not necessarily correlate with favorable distal cerebrovascular resistance, as measured by pulsatility index (PI). 2. This study recommends that patients with acute thrombotic stroke undergo a comprehensive examination to ensure an accurate diagnosis and appropriate treatment. Abstract Stroke is the second leading cause of death and disability in the world. Diabetes mellitus is a risk factor for stroke with an increase in blood viscosity associated with hyperglycemia, and HbA1c is a well-established biomarker primarily used for the long-term monitoring of glycemic control in patients with diabetes mellitus. The Pulsatility index (PI) parameter of Trans Cranial Doppler (TCD) can measure blood vessel resistance. This study was to prove the correlation between HbA1c and PI in Middle Cerebral Artery (MCA) of acute thrombotic stroke patients. A cross-sectional study was conducted to thrombotic stroke patients treated at the neurological ward of Dr. Soetomo General Academic Hospital, Surabaya, Indonesia from March 2019 to April 2020 who met the inclusion and exclusion criteria. Data were obtained from medical records. Statistical analysis was performed using Spearman test for numerical data and Chi-square for categorical data with a significant value of p <0.05. There were 32 subjects who met the inclusion and exclusion criteria. A total of 24 subjects (75%) were males and 8 (25%) females with a mean age of 56.41±13.22 years. PI MCA results were abnormal in 14 subjects (43.75%) with an average of 1.8±0.97 and PI MCA was normal in 18 subjects (56.25%) with an average of 0.87±0.15. The average HbA1c was 6.55±1.9%. There was no statistically significant association observed between HbA1c and PI in MCA examination (r=0.07; p=0.73). In conclusion, the findings of this study indicate the lack of correlation between pulsatility index and HbA1c in patients with acute ischemic stroke. This underscores the importance of comprehensive cerebrovascular evaluation regardless of HbA1c status.